(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research describes the reception oh generation regarding the meaning of the lyrics of the Minahasan ethnic song Si Patokaan. The method used in this research is descriptive qualitative. Data collection techniques re observation, interviews, documentation. The data analysis techniques used are analysis according to Pohan (Prastowo 2012: 208) data collection techniques are the methods used to collect information or facts in the field. The data collection technique is the most strategic step in research because it is the main aim of the word zoomer because they were born and grew up along with rapid technological developments. Types of meaning: Lexical meaning is real meaning in accordance with our lives. Grammatical meaning is often called contextual meaning or situational meaning. Cultural meaning arises from the relationship between one conversation and another. A mother’s concern for her child who has grown up and gone far away to earn a living.